A new species of Cinnamomum and notes on the status of C. palghatensis in Western Ghats, India - Geethakumary, M. P.; Deepu, S.; Pandurangan, A. G. (Phytotaxa, 2017)
Cinnamomum gamblei, a new species of Lauraceae is described from Western Ghats, India. The new species resembles C. macrocarpum by having large fruit, but is easily recognized by its habit, leaf morphology, shape and size of tepals and 4-locellate stamens in whorl III. A detailed description along with images, distribution details, comparison with related species and other relevant notes are provided for its easy identification. The status of C. palghatensis is also discussed here.